ZAINTERESOWANIA JĘZYKOZNAWCZE ZYGMUNTA KRASIŃSKIEGO - LEWASZKIEWICZ, TADEUSZ (Slavia Occidentalis, 2020)
Zygmunt Krasiński devoted much if his attention to the “philosophical” essence of the language and the origins of various tongues. His conjectures, based on speculative and mystic philosophy, are of no scientific importance; rather, they reflect the author’s strong attachment to religion. While not original, his views on the role of a mother tongue in preserving national identity are correct. The writer was interested in spelling and correct grammatical usage of the Polish language. He also focused on assessing the style of texts written in Polish and French. His views were hardly innovative, offering some value in comparison with the 19th century theory of style. Other language-related mentions: the sophistication of Juliusz Słowacki’s language and proposals of baby names based on “inspired” etymological ideas, are inconsequential.